Nanosheet-assembled MoSe2 and S-doped MoSe2−x nanostructures for superior lithium storage properties and hydrogen evolution reactions1. Issue 10 (29th October 2015) - Yang, Yong; Wang, Shitong; Zhang, Jingchao; Li, Haoyi; Tang, Zilong; Wang, Xun
<x xml:space="preserve">Abstract</x> The development of layered molybdenum chalcogenides with largely exposed active sites is receiving intense interest because of their potential applications in energy storage and catalysis.